A three-phase contact-breakage model for brittle spherical particles with conical nucleus formation - Yiran Niu; Jiaquan Liu; Haiying Guo; Huawei Yang (Scientific Reports)
Abstract A novel contact-breakage (CB) model is proposed to characterize the complete breakage process of brittle spherical particles, with particular emphasis on the critical role of conical nucleus formation. Unlike conventional elastic models, the CB model incorporates three distinct mechanical phases: local compaction, elastic deformation, and integral crushing. The model introduces a crushing modulus to quantify the relationship between compacted volume and contact force during local compaction, while adapting a strength criterion for brittle materials to determine integral crushing. Experimental validation through particle contact tests demonstrates the model’s superior predictive capability in determining conical nucleus dimensions, force–deformation relationships, and failure forces compared to traditional elastic models. This study provides new insights into particle breakage mechanisms, offering significant implications for engineering applications involving coarse-grained soils.